1973
DOI: 10.1007/bf02397911
|View full text |Cite
|
Sign up to set email alerts
|

The tensile fracture behaviour of the aligned Al-Al3Ni and Al-CuAl2 eutectics at various temperatures

Abstract: The tensile behaviour of single crystals of the unidirectionally-solidified AI-AI3Ni fibrous and AI-CuAI2 lamellar eutectics has been investigated at ambient and elevated temperatures. Fractured specimens have been studied directly by scanning electron microscopy, and longitudinal sections through each fracture surface by optical microscopy. At low temperatures, fracture of the AI-AIzNi eutectic is caused by the brittle failure of AI3Ni fibres. At intermediate temperatures broken fibres may be present without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
12
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 13 publications
(8 reference statements)
2
12
0
Order By: Relevance
“…As may be expected from these photographs, fracture surfaces of the axis, irrespective of deformation temperature. This certainly suggests, as pointed out also by Cantor et al (5), that local stresses due to the fiber break are transmitted to an adjacent fiber the tensile axis. Such the plastic shear, which should be due to dislocation activity, may be ascribed to good ductility of the Al matrix and Micro-void formation (that is, crack origination) will be discussed here in connection with a mode of fiber break.…”
Section: Fracture Processessupporting
confidence: 56%
See 1 more Smart Citation
“…As may be expected from these photographs, fracture surfaces of the axis, irrespective of deformation temperature. This certainly suggests, as pointed out also by Cantor et al (5), that local stresses due to the fiber break are transmitted to an adjacent fiber the tensile axis. Such the plastic shear, which should be due to dislocation activity, may be ascribed to good ductility of the Al matrix and Micro-void formation (that is, crack origination) will be discussed here in connection with a mode of fiber break.…”
Section: Fracture Processessupporting
confidence: 56%
“…Since, at least at low temperatures, the aligned Al-Al3Ni eutectic exhibits no macroscopic local necking prior to fracture (5), it is rather difficult to find out an initial site of micro-void formation (that is, a site of crack initiation), remarkably. Two types of stress lowering, which should reflect a fracture mode, can be seen in Fig.…”
mentioning
confidence: 99%
“…The microstructure study as reported by Butcher et al [26] shows coarsening of the eutectic. Work by Cantor et al [11,12] clearly explains the mechanical behavior of Al-Al 2 Cu at elevated temperature. In order to understand the effect of temperature on microstructure, and hence on mechanical properties, a comparison plot of yield stress as a function of temperature is presented in Figure 4a.…”
mentioning
confidence: 88%
“…Sc are among the most intensively studied in situ eutectic composites. However, the structural applications of these alloys are limited due to their poor room-temperature ductility [11][12][13].Non-equilibrium processing provides an opportunity to produce materials with a bimodal microstructure having a nanometer length scale containing a high volume fraction of intermetallic phases. Such alloys can exhibit high strength and reasonably high ductility at room temperature.…”
mentioning
confidence: 99%
See 1 more Smart Citation